De novo synthesis of hybrid d–f block metal complex salts for electronic charge transport applications. Issue 4 (6th January 2022) - Mahato, Shreya; Mondal, Amit; Das, Mainak; Joshi, Mayank; Ray, Partha Pratim; Roy Choudhury, Angshuman; Reddy, C. Malla; Biswas, Bhaskar
Abstract : The work demonstrates the introduction of hybrid d–f block complex salts of the type M(ii )–Ce(iv ) and their charge-transport behaviour. Abstract : The advent of d–d type complex salts for designing smart functional materials with versatile utility inspired us to develop a novel type of M(ii )–Ce(iv ) complex salts [M(ii ) = Cu and Zn ions]. In this study, we present for the first time a holistic approach to design and prepare metal complex salts of the novel hybrid d–f block type, [Cu(bpy)2 ]2 [Ce(NO3 )6 ]2 (1 ), [Cu(phen)2 (NO3 )]2 [Ce(NO3 )6 ](HNO3 ) (2 ), [Zn(bpy)2 (NO3 )][ClO4 ] (3 ), and [Zn(phen)2 (NO3 )]2 [Ce(NO3 )6 ] (4 ); [bpy = 2, 2′-bipyridine; phen = 1, 10-phenanthroline]. The intrinsic structural and morphological properties of the compounds have been revealed by employing a suite of analytical and spectroscopic methods. X-ray structural analysis reveals that the copper(ii ) centres in the cationic complex units of 1 and 2 adopt a highly distorted tetrahedral and a rare bicapped square pyramidal coordination geometry, respectively. The zinc(ii ) ions in both 3 and 4 adopt the rare bicapped square pyramidal geometry while the cerium(iv ) ions in 1, 2 and 4 exist in a dodecahedral geometry. Investigation of supramolecular interactions reveals that intermolecular O⋯H and O⋯π short contacts bind the complex units in 1, while predominant π⋯π interactions, along with O⋯H and O⋯π short contacts, produce the binding force among the complex units in 2 . We further employed the complex salts (1–4 ) to construct Schottky devices to reveal the role of these new complex salts in the charge-transport phenomenon. The carrier mobilities ( μ ) for salts 1–4 were determined to be 1.76 × 10 −6, 9.02 × 10 −6, 1.86 × 10 −8, and 4.31 × 10 −8 m 2 V −1 s −1, with respective transit times ( τ ) of 439, 85, 4.17 × 10 3, and 1.79 × 10 3 ns, which suggest that complex salt 2 is the best candidate with the highest transport properties among all the complex salts. A crystal engineering perspective sheds light on the charge-transport properties of the complex salts, emphasizing the attribution of the best performance of 2 to its predominant π⋯π interactions. The synthesis of this new type of complex salts, their physicochemical properties and their charge-transport applications envisage great promise for the development of novel crystalline materials with smart functionalities.